Adding a piece to the puzzle of Latin American blood donors and the potential risk of Trypanosoma cruzi transmission in Germany - Ullrich, Julian; Guertler, Lutz; Quenzel, Ernst; Weinauer, Franz; Rößler, Dieter; Kalus, Ulrich; Pruß, Axel; Albajar-Viñas, Pedro; Pritsch, Michael (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction. Chagas disease (CD) is caused by the Trypanosoma cruzi (T. cruzi) infection and has become a global health concern due to population mobility, as well as non-vectorial transmission routes. Several countries outside Latin America (LA) have reported transfusion-associated transmission, but equivalent studies in Germany are lacking. This study aims to collect first data on the risk of transfusion associated transmission as well as LA blood donors originating from CD endemic countries in Germany. Materials and methods. A total of 305 blood donors who were assumed to be at risk for T. cruzi infection were retrospectively (267) as well as prospectively (38) selected at German blood donation sites in Bavaria and Berlin, and all retrospectively as well as 27 prospectively selected were serologically screened. Prospective study subjects additionally filled out a questionnaire. Results. All samples tested seronegative for T. cuzi specific antibodies. Prospectively enrolled study subjects all had high socio-economic status including good education. Knowledge regarding CD was limited but willingness to donate frequently was high. Blood donation rates from donors born in LA countries seem to increase from 2015. Discussion. Although no transfusion associated T. cruzi infection has been documented in Germany, it has likely already happened unnoticed, or will do in the near future. Performing risk-adapted serology-based blood donor screenings in Germany could avoid transfusion-associated transmission events as well as contribute to active case detection. Moreover, larger, and ongoing studies are needed to increase the evidence base as well as end the neglect of CD in Germany.